What's a SNP between friends: the influence of single nucleotide polymorphisms on virulence and phenotypes of Clostridium difficile strain 630 and derivatives - Collery, Mark M.; Kuehne, Sarah A.; McBride, Shonna M.; Kelly, Michelle L.; Monot, Marc; Cockayne, Alan; Dupuy, Bruno; Minton, Nigel P. (Taylor & Francis, 2016)
Clostridium difficile is a major cause of antibiotic induced diarrhoea worldwide, responsible for significant annual mortalities and represents a considerable economic burden on healthcare systems. The two main C. difficile virulence factors are toxins A and B. Isogenic toxin B mutants of two independently isolated erythromycin-sensitive derivatives (630E and 630Δerm) of strain 630 were previously shown to exhibit substantively different phenotypes. Compared to 630, strain 630E and its progeny grow slower, achieve lower final cell densities, exhibit a reduced capacity for spore-formation, produce lower levels of toxin and are less virulent in the hamster infection model. By the same measures, strain 630Δerm and its derivatives more closely mirror the behaviour of 630. Genome sequencing revealed that 630Δerm had acquired seven unique Single Nucleotide Polymorphisms (SNPs) compared to 630 and 630E, while 630E had nine SNPs and a DNA inversion not found in the other two strains. The relatively large number of mutations meant that the identification of those responsible for the altered properties of 630E was not possible, despite the restoration of three mutations to wildtype by allelic exchange and comparative RNAseq analysis of all three strains. The latter analysis revealed large differences in gene expression between the three strains, explaining in part why no single SNP could restore the phenotypic differences. Our findings suggest that strain 630Δerm should be favoured over 630E as a surrogate for 630 in genetic-based studies. They also underline the importance of effective strain curation and the need to genome re-sequence master seed banks wherever possible.